EFEKTIVITAS PEMBELAJARAN TAHFIZ AL-QUR’AN SECARA TATAP MUKA PADA MASA PANDEMI COVID-19 DI MTS AL-JAUHAR GUNUNGKIDUL YOGYAKARTA - Roihatul Jannah (JIP: Jurnal Ilmu Pendidikan, 2024)
The COVID-19 pandemic forces companies to learn in a situation where they are afraid of getting the virus. The psychological state of a person in this pandemic era is more fearful, apprehensive, and nervous. This will definitely have an effect on the learning process's performance. The reason behind it is that learning should be done in a peaceful environment in order to achieve optimal benefits. Excessive worry in a student will cause him to have a negative self-image and lose motivation to study. This study employs a descriptive approach and a qualitative method. Interviews, documentation, and observation were used to obtain data for this study. Data reduction, data presentation, and verification were used to examine the information. Face-to-face learning performed by MTs Al-Jauhar during the period of the pandemic is found to be positive in this thesis. The average grade VIII students scored 75.6 for recitation in the medium category (achieved), 74.4 for tartiles in the moderate category (achieved), 71.7 for fluency in the mutqin category (achieved), and 2.2 for achieving the desired number of juz, according to the findings of this survey (achieved). MTs students, on the other hand, are in good psychological shape. This research shows that learning in the age of the COVID-19 pandemic may be effective if health protocols are followed correctly.